Decisions To Be Taken in the Use of Polygraph Examinations for Verifying Complaints About Violence: Analysis and Policy Recommendations1. Issue 2 (21st January 2013) - Ginton, Avital; Roach, Jason
Abstract The paper introduces the basic logic and assumptions underlying the most widespread polygraph technique, the Comparison Question Test. It then indicates that two of these assumptions encounter difficulties in cases involving victims of violence, which could increase the danger of error on the test. To handle this problem, it is required to take a few decisions related to specific professional procedures as well as to implement a special policy. Another line of problems stems from ethical considerations. The main point in this respect is that being polygraphed is quite an unpleasant experience. This is more so when the examinee is an authentic victim of violence whose complaint is under investigation. Polygraphing such a person adds to the suffering of the victim. The ethical question becomes a practical one, namely how to determine the situations in which polygraph examination on an alleged victim is, nevertheless, justifiable and differentiate them from other situations. A conceptual cost–benefit analysis is presented in this regard, and the need for taking specific decisions by the polygraph examiner, the criminal investigator, and the commanding officer, when facing the option of using the polygraph for investigating complaints about violence, is pointed out, together with a recommended policy. Copyright © 2013 John Wiley & Sons, Ltd.